Archive of Jewish History (Academic Studies Press, 2023)
Volume 12 of the Archive opens with a study by Yefim Melamed (Kyiv) about the history of Stalin's security services overseeing Jewish writers in the late 1930s and early 1950s resulted in repressions and the killing of many of them. The appendix to his article presents a unique material: the reports of a secret agent who reported on the activities of the "brothers in writing." Grigory Kan (Moscow) contributes to the study of the interminable topic: the Jews and the Russian revolution. His research is dedicated to Aaron Zundelevich (1852-1923), a prominent figure in the narodnik's movement, a member of the Executive Committee of the "People's Will." Roberta de Giorgi (Udine, Italy) focuses in her research on the history of translations and publicationa of Leo Tolstoy's Three Tales, the proceeds of which the author, at the request of Sholem Aleichem, donated to the Jews who suffered from the pogrom in Chisinau. The story turned out to be extremely confusing and fascinating and adds new touches to the biographies of L. N. Tolstoy and Sholem Aleichem, as well as to the history of literary life and publishing at the beginning of the 20th century. In her article, Maria Gulakova (St. Petersburg) publishes a letter from ethnographer and public figure Moses Krol (1862-1942) to Chaim Zhitlovsky. Information contained in a letter from Krol (then an émigré in Paris), dated March 26, 1936, sheds light on a little-known attempt to organize the resettlement of European Jews in the 1930s to Ecuador. Gulakova's research is based on materials collected from various archives in Moscow, Kyiv, New York, Jerusalem and Leeds.